JFQ volume 20 issue 1 Cover and Back matter (Journal of Financial and Quantitative Analysis, 1985)
Value maximization as a decision criterion is integrated throughout this new text, especially in the working capital section. Also included is a complete chapter on analysis of project risk. Examples apply finance concepts to the real-life concerns of financial managers in every chapter. Accompanied by a microcomputer, floppy-disk workbook with challenging problem sets.